The effect of sleep hygiene on sleep quality of people with type 2 diabetes mellitus - Jamini, Theresia (Sean Institute, 2024)
Patients with Type 2 Diabetes Mellitus (DM) have clinical symptoms such as polydipsia, polyuria, and pain, which also occur at night and can cause sleep disturbances. This sleep disturbance will increase the frequency of awakening, difficulty falling asleep again, and sleep dissatisfaction, which causes the quality of sleep to decrease. Sleep hygiene is a method to improve sleep quality in the form of a list of things that can facilitate and maintain sleep initiation. This study aims to determine the effect of sleep hygiene on the sleep quality of people with type 2 diabetes in the working area of Banjarmasin Indah Public Health Center. This quantitative study has a pre-experimental research design and a one-group pretest-posttest design. The sample in this study amounted to 29 respondents and was selected based on inclusion criteria. The measuring instrument used the Pittsburgh Sleep Quality Index (PSQI) questionnaire to measure sleep quality. In addition, the data was analyzed using the Wilcoxon test. The analysis results showed a significant difference between before and after sleep hygiene intervention (p-value = 0.000), so it can be concluded that sleep hygiene affects the sleep quality of people with Type 2 diabetes. Based on these results, community nurses at Banjarmasin Indah Public Health Center expected to include sleep hygiene in health education given to people with type 2 diabetes and their families.